A Discussion of Dawn Langan Teele's Field Experiments and Their Critics: Essays on the Uses and Abuses of Experimentation in the Social Sciences. Issue 4 (28th December 2016) - Sinclair, Betsy
Abstract : Experimental approaches to political science research have become increasingly prominent in the discipline. Experimental research is regularly featured in some of the discipline's top journals, and indeed in 2014 a new Journal of Experimental Political Science was created, published by Cambridge University Press. At the same time, there are disagreements among political scientists about the limits of experimental research, the ethical challenges associated with this research, and the general model of social scientific inquiry underlying much experimental research. Field Experiments and Their Critics: Essays on the Uses and Abuses of Experimentation in the Social Sciences, edited by Dawn Langan Teele (Yale University Press 2015), brings together many interesting perspectives on these issues. And so we have invited a number of political scientists to comment on the book, the issues it raises, and the more general question of "the uses and abuses of experimentation in the social sciences."